Comparison of the efficacy and safety of bimatoprost (0.03 %) and travoprost (0.004 %) in patients with primary open angle glaucoma - Chander, Ashish; Kapoor, H; Thomas, S (Nepalese Journal of Ophthalmology, 2013)
Purpose: To compare the efficacy and safety of bimatoprost (0.03 %) and travoprost (0.004 %) in patients with primary open angle glaucoma (POAG). Subjects and methods: Patients with POAG were randomized to receive either bimatoprost or travoprost once daily. Detailed ocular examination was done and intraocular pressure (IOP) was measured at 9.00 am, 1.00 pm and 4.00 pm at the baseline and at 1, 2, 4, 6 and 12 weeks of therapy. Results: A total of 31 patients were analysed. The patients were randomly divided into two groups (Bimatoprost group = 16; Travoprost group = 15). Both the groups had a statistically significant reduction from the baseline IOP at all follow up visits at 9.00 am, 1.00 pm and 4.00 pm. The mean IOP decreased from a baseline of 25 ± 2.32 mm Hg to 15.93 ± 1.79 mm Hg after 12 weeks in the bimatoprost group (p < 0.001), and from 24.2 ± 1.60 mm Hg to 16.53 ± 1.56 mm Hg in the travoprost group (p < 0.001). A better mean reduction of IOP was obtained with bimatoprost than with travoprost at the end of the study at 12 weeks (p = 0.03). Mild ocular redness was the commonest side effect in both the groups but was not significant in either group. Conclusion: Both drugs lowered IOP effectively but bimatoprost showed a greater reduction in the mean IOP than did travoprost at 12 weeks and both are safe for ocular use. Nepal J Ophthalmol 2013; 5(9):75-80 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7831